Mengembangkan Kegiatan Finger Painting untuk Meningkatkan Motorik Halus Pada Anak Usia 4-5 Tahun - Lili Fitri; Baik Nilawati Astini; Ika Rachmayani; Fahruddin Fahruddin (Indonesian Journal of Elementary and Childhood Education, 2021)
This research was motivated by the results of observations in the Otak Desa Village Central Lombok related to the fine motoric development of children who are still not optimally developed. This can be seen from the lack of optimal ability of children in moving their fingers, eye and hand coordination. The problem in this study is how to develop finger painting activities to improve fine motor skills in children aged 4-5 years in the Otak Desa Village Central Lombok in 2020. The purpose of this study is to improve the fine motor development of children aged 4-5 through finger painting activities in the Otak Desa Village Central Lombok. This type of research is development research. Subject in this study were 4 children consisting of one girl and three boys. The data analysis technique used qualitative descriptive data analysis. To obtain data in this study using observation and documentation methods. The results showed that at the first stage of development, the average value was 62,5%, while in the second development stage the average value reached 82,95% and has exceeded the desired target of 76%. Based on the results of this study, it can be concluded that developing finger painting activities can improve the fine motor skills of children aged 4-5 years in the Otak Desa Village Central Lombok in 2020.